Sources of Students’ Errors in EFL Writing in Indonesia - Elsa Widya Hapsari; Sudarman Sudarman; Sri Utami (JADEs Journal of Academia in English Education, 2022)
The purpose of this review paper is to compile studies related to the sources of errors made by Indonesian students in a writing skill, to summarize some prior findings in order to provide updated literature on error analysis, to identify difficulties that Indonesian students face in an EFL writing context, and to investigate the factors that influence writing success and failure. The results showed that three major factors contribute to students' errors in EFL writing in Indonesia: the influence of the first language on writing, large class sizes, and a lack of writing practice. This is reasonable, as studies have demonstrated that despite years spent in school learning English, a significant number of errors can still be found in writing products composed by university students. Therefore, the teacher can use several strategies, including implementing a specific learning strategy that affects the target language, reducing the number of students in the class so that they have enough time to practice writing based on the writing process, and providing better instruction in the structure and grammar sections. Furthermore, teachers should spend more time and effort outside of the classroom to help students receive feedback, particularly through conferencing.